ADSORPTION OF Pb(II) BY POLYANILINE/SILICA GEL COMPOSITE: KINETICS AND ISOTHERM STUDIES - Mas Inda Putrinesia; Nurlina Nurlina; Winda Rahmalia (Tanjungpura University, 2018)
Research on the study of kinetics and isotherm adsorption of Pb(II) by polyaniline/silica gel (PANI/SiO2) composite from glass waste has successfully been done. The polymerization of silica gel was prepared by sol-gel process. Meanwhile, PANI/SiO2 composite was prepared using sulfuric acid (H2SO4) as its dopants and hydrogen peroxide (H2O2) for oxidation process. Composition of oxide compound in PANI/SiO2 composite was analyzed by X-Ray Fluorosence (XRF) and Gas Sorption Analyzer (GSA). Adsorption of Pb(II) was carried out by contacting PANI/SiO2 with Pb(NO3)2 solution for 20, 40, 60 and 80 minutes, with concentrations of 150, 200, 250, 300, 350 and 400 mg/L. The optimum contact time was reached at 40 minutes. This adsorption followed pseudo-second order model with R2= 0.996. The first optimum adsorption capacity was reached in the concentration of 250 mg/L. Isotherm adsorption followed Langmuir models with R2= 0.954 (monolayer capacity= 51.02 mg/g).